Synthesis of stereoisomers of Artemisia and Chrysanthemum bis(acetylenic) enol ether spiroacetals. - Wu, B; Feast, G; Thompson, A; Robertson, J (2012)
An 11-step synthesis is described of two diastereomeric candidates for a bis(acetylenic) enol ether spiroacetal isolated from Chrysanthemum boreale. Key steps in the synthetic route include spiroacetal lactone alkylidenation and subseqent modified Cadiot-Chodkiewicz cross-coupling to install the bis(acetylenic) enol ether functionality. From NMR comparisons, neither of the candidates, whose structures were confirmed by single-crystal X-ray diffraction, correspond to the natural product, and a proposal for the correct structure is put forward.